Estrutura da variação craniana em populações de Bolomys lasiurus (Lund, 1841) (Rodentia: Cricetidae) do Nordeste do Brasil - Oliveira, João Alves de (1992)
Cranial variability within and among populations of the akodont rodent Bolomys lasiurus from Northeastern Brazil is investigated. ln a first step, the correlation structures between tooth wear and suture ossification indexes are evaluated to access possible effects of sex, vegetation, season and local variation among samples of 31 sites on craniodental estimators of rela tive age and to improve age determination for quantitative analyses. Non-geographic (age and sexual) variation in 30 cranial measurements is analysed and possible determinants of the reduction of the number of sexually dimorphic characters through consecutive age classes are investigated. The structure of covariance among cranial traits was summarized by the coefficients of the first eigenvector extracted from the covariance matrix for each population sample. Comparison of the covariance structure among populations reveals an underlying pattern in the trajectory of post-natal development, in spite of significant differences in character means. Models of phenotypic evolution were employed to assess the role of evolutionary forces that might have acted to produce the observed differentiation among populations. The null hypothesis of genetic drift is not refuted.